Evaluation of user concentration in ubiquitous and cognitive artificial intelligence‐assisted English online guiding system integrating face and eye movement detection. (20th August 2020) - Liu, Lu; Peng, Nan
Summary: In recent years, artificial intelligence technology has made significant breakthroughs. Big data, cloud computing, speech recognition, deep learning, and so on have become new hot spots after the Internet of things. The rapid development of artificial intelligence technology promotes the innovation of foreign language teaching ideas and learning methods. The new ecology and new paradigm of foreign language guiding must be reconstructed. The biggest difference between the Internet of things and the Internet is that the Internet of things is directly connected with all kinds of sensors. It does not need people to input information through the keyboard but automatically obtain information and carry out automatic processing. The deep integration of smart classroom and English online teaching will help to promote the reform and innovation of English teaching and provide a new way for the development of English online teaching. In this paper, we analyze the fusion of face recognition technology and eye tracking system and analyze the user focus evaluation theory in the Internet of things environment. Based on the above technology, this paper proposes an online English teaching user focus evaluation system in the context of artificial intelligence. Abstract : Artificial intelligence technology has made significant breakthroughs. Big data, cloud computing, speech recognition, deep learning, and so on have become new hot spots after the Internet of things. In this paper, we analyze the fusion of face recognition technology and eye tracking system and analyze the user focus evaluation theory in the Internet of things environment. Based on the above technology, this paper proposes an online English teaching user focus evaluation system in the context of artificial intelligence.